Comprehensive epidemiological and genotype–phenotype analyses in a large European sample with idiopathic achalasia. Issue 6 (June 2016) - Becker, Jessica; Niebisch, Stefan; Ricchiuto, Arcangelo; Schaich, Eva J.; Lehmann, Gavin; Waltgenbach, Tobias; Schafft, Annette; Hess, Timo; Lenze, Frank; Venerito, Marino; Hüneburg, Robert; Lingohr, Philipp; et al.
Abstract : Background and aim: Although an eight-residue insertion in HLA-DQβ1 has been recently identified as a genetic risk factor for idiopathic achalasia, other risk factors are still unknown. In the present study, we carried out an epidemiological survey and a genotype–phenotype (G×P) analysis to gain further insights into the etiology of achalasia. Methods: We obtained medical data from 696 achalasia patients and 410 controls, as well as their first-degree relatives (2543 of patients and 1497 of controls). For the G×P analysis, we stratified the patients into HLA-DQβ1 insertion carriers and noncarriers. Results: Our data show that patients are more often affected by viral infections before achalasia onset ( P <0.0001, most significantly for varicella zoster virus infections). In addition, allergic ( P =0.0005) and autoimmune disorders ( P =0.0007, most significantly for psoriasis and Sjögren's syndrome) represent comorbid disease conditions. First-degree relatives of patients also show higher prevalence rates of allergic disorders ( P =0.0007) and psoriasis ( P =0.016) compared with control relatives. Moreover, the G×P analysis reveals that achalasia is triggered by pregnancies in female HLA-DQβ1 insertion carriers ( P =0.031). Conclusion: Our data point to a role of viral infections in the development of achalasia. In addition, they provide evidence for a relationship between achalasia and allergic, as well as autoimmune, disorders. Furthermore, pregnancy seems to be a disease-triggering factor in female HLA-DQβ1 insertion carriers, which points to hormonal and/or immunosuppressive factors influencing disease development. Abstract : Supplemental Digital Content is available in the text.